2016
DOI: 10.1002/pc.24053
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and frictional properties of mesoporous silica SBA‐15/phenolic resin nanocomposites

Abstract: Mesoporous silica SBA-15/phenolic resin hybrid materials (SBA-15/PF) were fabricated through in situ polymerization of phenol and formaldehyde in the presence of SBA-15 and subsequent SBA-15/PF nanocomposites were prepared by compression moldings. The results revealed that the glass transition temperatures and thermal stability of SBA-15/PF hybrid materials were obviously enhanced compared to pure PF. In addition, the dynamic mechanical and friction properties of SBA-15/PF nanocomposites were improved remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…In terms of piezoelectric PVDF, according to the literature, 35 the addition of PCL could enhance the β‐phase content of PVDF, while to the best of our knowledge, up till now, no studies have been conducted on the effect of mesoporous silica particles on the piezoelectric properties of PVDF. It was shown that the physical properties of polymers, such as thermal and mechanical properties are affected by the addition of mesoporous silica particles; some researchers have reported that mesoporous silica particles can change the glass transition temperature ( T g ) of a polymer matrix and enhance its dynamic mechanical properties 32,33,36–40 as well as thermal stability 29,34,36–44 . Very little research has been reported on the influence of mesoporous silica on the miscibility of polymer blends.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of piezoelectric PVDF, according to the literature, 35 the addition of PCL could enhance the β‐phase content of PVDF, while to the best of our knowledge, up till now, no studies have been conducted on the effect of mesoporous silica particles on the piezoelectric properties of PVDF. It was shown that the physical properties of polymers, such as thermal and mechanical properties are affected by the addition of mesoporous silica particles; some researchers have reported that mesoporous silica particles can change the glass transition temperature ( T g ) of a polymer matrix and enhance its dynamic mechanical properties 32,33,36–40 as well as thermal stability 29,34,36–44 . Very little research has been reported on the influence of mesoporous silica on the miscibility of polymer blends.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal decomposition temperatures (T d ) determined by TGA and the Tg determined by DSC of SBA-15/phenolic resin hybrid materials (SBA-15/ phenolic resin [PF]) fabricated through in situ polymerization of phenol and formaldehyde in the presence of SBA-15. 80 From DSC scans, the Tg of pure PF was 82.08°C. Subsequent scans of PF containing different loadings of SBA-15 exhibited higher Tg values.…”
Section: Nanocomposite Propertiesmentioning
confidence: 99%
“…These type of resins are made from phenols and aldehydes (more especially formaldehyde) that can be synthesized by acid-catalysis (novolacs) or base-catalysis (resoles) approaches through step-growth copolymerization reaction. [1][2][3][4] Novolacs are useful in a wide range of industrial applications including, coatings, molded pieces and articles, composite matrices, foam material, and electronic industries mainly because of their superior features such as good chemical and corrosion resistance, excellent hardness, solvent and moisture resistances, excellent thermal behavior (eg, heat resistance, low flammability, and slow heat release), and extremely low generation of toxic gases that stimulate their contribution to further market growth. [5][6][7] In general, hexamethylenetetraamine (HMTA) is the most widely used curing agent, along with heating to produce highly crosslinked novolacs.…”
Section: Introductionmentioning
confidence: 99%
“…Blending with elastomers and thermoplastics, 2. Monomer modification (eg, cardanol, cardol, and anacardic acid), 3. Reducing crosslink density, and 4.…”
Section: Introductionmentioning
confidence: 99%